Analisis faktor-faktor yang mempengaruhi struktur modal di Bursa Efek Indonesia - Hendi Hendi; Yenny Susanti (Jurnal Ekonomi Modernisasi, 2021)
Capital structure is a combination of capital and debt so that it is very influential on the company's financial position. To finance operations, companies can use funds from debt or capital. However, the company's management must know whether the company is able to bear the financial risks or costs of these funds to prevent the company's bankruptcy. The purpose of this research is to analyze the factors that influence the capital structure. The independent variables are corporate tax rates, non-debt tax savings, investment opportunity sets, sales growth, and profitability. The sample data tested were obtained from the annual reports of companies listed on the Indonesia Stock Exchange (IDX). The reporting period used in this study was five years and amounted to 2,210. The data obtained were then processed through the SPSS 25 and Eviews 10 systems. The results revealed that corporate tax rates and profitability have a significant negative effect on capital structure. There is a significant positive effect of the investment opportunity set variable and sales growth on the owned capital structure. Another finding is that non-debt tax savings have no significant effect on capital structure.